4',5-dihydroxy-7-methoxyflavanone dihydrate - Brito, Iván (2012)
The title compound, C 16H 14O 5· 2H 2O [systematic name: 5-hydroxy-2-(4-hydroxyphenyl)-7- methoxychroman-4-one dihydrate], is a natural phytoalexin flavone isolated from the native chilean species Heliotropium taltalense and crystallizes with an organic molecule and two water molecules in the asymmetric unit. The 5-hydroxy group forms a strong intramolecular hydrogen bond with the carbonyl group, resulting in a six-membered ring. In the crystal, the components are linked by O-H··· O hydrogen bonds, forming a three-dimensional network. The 4-hydroxyphenyl benzene ring is bonded equatorially to the pyrone ring, which adopts a slightly distorted sofa conformation. The title compound is the hydrated form of a previously reported structure [Shoja (1990). Acta Cryst. C46, 1969-1971]. There are only slight variations in the molecular geometry between the two compounds.